When Casimir meets Kibble-Zurek - Vacanti, G; Pugnetti, S; Didier, N; Paternostro, M; Palma, G; Fazio, R; Vedral, V (2012)
Verification of the dynamical Casimir effect (DCE) in optical systems is still elusive due to the very demanding requirements for its experimental implementation. This typically requires very fast changes in the boundary conditions of the problem. We show that an ensemble of two-level atoms collectively coupled to the electromagnetic field of a cavity, driven at low frequencies and close to a quantum phase transition, stimulates the production of photons from the vacuum. This paves the way for an effective simulation of the DCE through a mechanism that has recently found experimental demonstration. The spectral properties of the emitted radiation reflect the critical nature of the system and allow us to link the detection of DCE to the Kibble-Zurek mechanism for the production of defects when crossing a continuous phase transition. © 2012 The Royal Swedish Academy of Sciences.